Analisis Kaligrafi Kontemporer Dari Aspek Keterbacaan Huruf Dan Warna - Tia Agustin; Anam Ibrahim (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This research was conducted because the research conducted found findings in contemporary calligraphy works in SMP Negeri 15 Integrated Islamic Binjai are some of the work of students who do not meet the right color mix, in the mix of readability of letters are still unreadable, excess in letters, and calligraphy works are still commonly found Error with letter update. This study discusses to discuss, study, discuss, analyze and analyze color selection and letter readability in contemporary calligraphic works by extracurricular students in Binjai Integrated Islamic Middle School 158 from 2018 to 2019. This study uses qualitative question and answer according to search. The subject of this research is the contemporary work of extracurricular students in terms of letters and color reading of 8 contemporary calligraphy works. The overall results in this study explain about contemporary calligraphy works that discuss the openness of letters and colors quite well. With an average value of 81.05 for letter readability and 80.42 for color.